The authority of principals’ technology leadership in empowering teachers’ self-efficacy towards ICT use - Siti Noor Ismail; Mohd Norakmar Omar; Arumugam Raman (Institute of Advanced Engineering and Science, 2021)
The application of information technology and communication (ICT) in education has a significant impact on teachers. Administrators pressure them to use ICT to improve the quality of teaching and to learn in the classroom. However, teachers are still skeptical of the ability to embody pedagogical strategies through the use of ICT. The purpose of this study was to explore the relationship between principals’ technology leadership and teachers’ self-efficacy. The study also determined the dimensions of technology leadership that are predictors to the empowerment of teachers' self-efficacy in using ICT. There are two instruments used, namely NETS-A and TSES. The respondents of the study consisted of 376 teachers in Malaysia. The study was conducted based on a quantitative approach, and respondents were selected through multi-level sampling. The results of the t-test found no significant difference for the gender of teachers on the improvement of self-efficacy. Through correlation testing, there was a moderate relationship between technology leadership and teachers’ self-efficacy. Even so, there is 24% of the influence of technology leadership that affects teachers' self-efficacy. Two contributing dimensions are excellence in professional practice and digital citizenship. In summary, principals can generate a revival of teachers' self -efficacy if they wisely encourage them to use ICT. Principals should be role models to teachers and students in ensuring that the concept of pedagogy in the classroom is always carried out through an ICT approach.